A close-up on ‘top tweeters' in Finland: Relevance of the national context in political Twitter campaigning - Railo,Erkka (2017)
This article examines the use of Twitter by Finnish candidates in the European parliamentary election of 2014. It concentrates on two groups of candidates: the 20 most active Twitter users measured by the number of tweets sent and those 20 candidates who aroused the most interest, measured by the number of Twitter replies received. The study takes into consideration contextual variables, such as gender, age, party, position and place of residence of the candidates. The main research question asks for what kind of candidates does Twitter offer a platform to challenge existing political power structures (equalizing hypothesis), and for what kind of candidates does Twitter not offer this platform (normalization hypothesis) The main finding was that Twitter was mostly used by established, middle-aged, urban, professional politicians of the right-wing National Coalition Party. This party has mostly young, well-educated and urban supporters in Southern Finland. For these people, Twitter was an effective tool to normalize the current power structures. However, for some other candidates Twitter seemed to have a more equalizing nature: the Green candidates, women and representatives of the parties' youth organisations. The article demonstrates the need for a more nuanced approach to the normalization/equalization hypothesis in future research.